Correlations between the Dielectric Properties and Exterior Morphology of Cells Revealed by Dielectrophoretic Field-Flow Fractionation - Gascoyne, Peter R. C. (2013)
Although dielectrophoresis (DEP) has great potential for addressing clinical cell isolation problems based on cell dielectric differences, a biological basis for predicting the DEP behavior of cells has been lacking. Here, the dielectric properties of the NCI-60 panel of tumor cell types have been measured by dielectrophoretic (DEP) field-flow fractionation, correlated with the exterior morphologies of the cells during growth, and compared with the dielectric and morphological characteristics of the subpopulations of peripheral blood. In agreement with earlier findings, cell total capacitance varied with both cell size and plasma membrane folding and the dielectric properties of the NCI-60 cell types in suspension reflected the plasma membrane area and volume of the cells at their growth sites. Therefore, the behavior of cells in DEP-based manipulations is largely determined by their exterior morphological characteristics prior to release into suspension. As a consequence, DEP is able to discriminate between cells of similar size having different morphological origins, offering a significant advantage over size-based filtering for isolating circulating tumor cells, for example. The findings provide a framework for anticipating cell dielectric behavior on the basis of structure-function relationships and suggest that DEP should be widely applicable as a surface marker-independent method for sorting cells.